THE STUDY OF ORGANIZATIONAL BEHAVIOR ON FISHERY MANUFACTURE INDUSTRIES EMPLOYEES PERFORMANCES - Handaru, Agung Wahyu; Mardiyati, Umi (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2014)
The purpose of this study was to examine the employee performance of fish-based food processing industries in West Java, which driven by variables of organizational culture, job satisfaction and motivation. The fishing industry in Indonesia has resulted in huge foreign exchange. On the other hand, their products are still poor quality and do not meet export standard. This is likely due to low employee performance. The research object were employees of three fish-based food processing plants. The sample was selected by simple random sampling technique. This study revealed different results from previous studies, that only organizational culture has an effect on employee performance. While job satisfaction and motivation has no effect on performance.Â Tujuan penelitian ini adalah menguji kinerja karyawan industri pengolahan makanan berbasis ikan di wilayah Jawa Barat, yang dipengaruhi dari variabel budaya organisasi, kepuasan kerja dan motivasi. Industri perikanan di Indonesia telahmenghasilkan devisa negara besar. Disisi lain, hasil produknya masih banyak yang belum memenuhi standar ekspor dan bermutu rendah. Hal tersebut kemungkinan dikarenakan kinerja karyawan yang rendah. Objek penelitian ini adalah karyawan dari tiga pabrik pengolahan makanan berbasis ikan. Sampel dipilih dengan teknik simple random sampling. Penelitian ini mengungkapkan hasil yang berbeda dari penelitian sebelumnya. Dari ketiga variabel independen, hanya budaya organisasi yang berpengaruh pada kinerja karyawan. Sedangkan kepuasan kerja dan motivasi tidak berpengaruh.